Factors contributing to organizational change acceptance among Gen Y Executives in PETRONAS Project Delivery and Technology Division / Siti Aminah Mohd Johan - Mohd Johan, Siti Aminah (Faculty of Business and Management, 2017)
Change is apparent now days in organization as the economic situation and other factors often forces company to consistently change in order to remain robust in their business operation. However, IBM (2008) found that approximately 41% of change projects were considered successful in meeting its objectives within planned time despite budget and quality constraints, compared to the remaining 59% of change projects that fail to reach at least one objective or failed entirely. Change is often unsuccessful when employee, the most impacted members of the organization decided to resist the change. Resistance to change is the outcome of negative acceptance of employee that is often caused by the fear of the unknown. The purpose of this research to investigate on the factors that influence organizational change acceptance among Gen Y Executives in PETRONAS Project Delivery and Technology Division. This study investigate the association of the variables that contributes to the organizational change acceptance among Gen Y Executives in PETRONAS Project Delivery and Technology Division. The research utilize descriptive study to describe the relationships between two variables. The population of the research is 2,403 executives. The sample size is 331 executives. Data were gathered through electronic questionnaire that is distributed to 900 randomly selected executives via email. The response rate of the survey is 86.7% where 287 responses were received. Only 221 responses is used to conduct quantitative data analysis. The study found that the executives hold fairly neutral acceptance towards the change. Only quality of information, employee participation, organizational support and threat appraisal have significant influence on organizational acceptance among Gen Y Executives.